PEMANFAATAN TEKNOLOGI KERTAS NANO KARBON SEBAGAI PEMBUNGKUS WORTEL - Dian Anggraini Indrawan; Novitri Hastuti, Lisna Efiyanti; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2018)
Indonesia’s paper consumption, including food wrapping-paper, might steadily increase in the future. This could someday upset the capability of domestic wrapping-paper production due to dwindling potency of conventional fibers (e.g. natural-forest wood). Alternative fibers are abundantly available and it mostly remains unutilized, than it should be introduced in industry, such as bamboo. This study aims to optimize the utilization of alternative fiber sources through the manufacture of wrapping paper from bamboo fiber using carbon nano technology as a foodstuff protector/wrapping. Relevantly, manufacturing trial on papers with nano-technology capability for carrot wrapping was conducted from two bamboo species tali (Gigantochloa apus) and ampel (Bambusa vulgaris) separately. Initially, each species was pulped semi-chemically, and then added with nano-sized activated charcoal particles (20%, w/w). The mixture (bamboo pulp + activated charcoal) was formed into sheets with targeted basic-weight common for wrapping-paper (60 g/m2), and then used for carrot wrapping and the physical strength properties was tested. Result shows that charcoal could can lower carrot-weight loss, which indicates high effectivity in maintaining the carrot freshness and nutritions. Papers made from ampel-bamboo fibers were more prospective for such wrapping than those made from bamboo tali. The use of any experimented papers for carrot wrapping was still better than without wrapping, as they afforded more in securing carrots.